Artificial Intelligence Adoption and Business Performance: The Mediating Role of Sustainable Competitive Advantage in the Food and Beverage Industry - Rodhiah; Aspiranti , Tasya; Amaliah, Ima; Nurhayati, Nunung (Yayasan Gema Bina Nusantara, 2025)
This research aims to analyze the impact of adapting Artificial Intelligence (AI) on business performance with mediating sustainable competitive advantage (SCA)in the Food and Beverage (F&B) industry located in West Jakarta. The population was all F&B companies in West Jakarta. The sample includes 120 respondents selected with purposive sampling, with criteria including respondents who understand and have adopted AI in their business operations for a minimum of three years. The data used Likert-scale questionnaires adapted from previously validated and reliable instruments. Data analysis using SEM by SmartPLS software. The results indicate that adapting AI has a positive but insignificant effect on the business performance of F&B companies in West Jakarta. Additionally, the study found that adapting AI has a positive and significant impact on sustainable competitive advantage, which in turn has a positive and significant effect on business performance. Mediation analysis revealed that sustainable competitive advantage mediates the relationship between adapting AI and business performance. This suggests that adapting AI does not directly affect business performance but rather indirectly through sustainable competitive advantage. Sustainable competitive advantage directly influences business performance. The conclusion of this research is that adapting AI is a crucial strategy for improving business performance through sustainable competitive advantage in the F&B industry in West Jakarta. Companies that invest in AI technology and integrate it into their business strategies have the potential to achieve superior performance by maintaining their sustainable competitive advantage in the long term.